ASEAN centrality : year of big power transitions - Ho, Benjamin Tze Ern (2012)
As the global community continues to grapple with political and economic uncertainties, ASEAN must resist the temptation to look inward if it is to maintain its much vaunted centrality amidst big power transitions.